Financial Derivatives: Fiscal Weapons of Mass Destruction - Wigan, Duncan (Politik, 2013)
Contemporary derivatives mark the development of capital and constitute a novel form of ownership. In abstracting from the object of ownership, the underlying asset, derivatives sever direct material ties be- tween the owner and property and, in doing, transform the capacities of ownership. is transformation is spatial, temporal and legal. is is signi cant for relations between borrowers and lenders, between the various participants in nancial markets, and, indeed, for the overarching institutional fabric of the politi- cal economy. However, one relatively neglected aspect of the transformations manifest through derivatives is the relationship between the scal state and nancial innovation. By recon guring the temporal, spatial and legal character of ownership derivatives present a substantive challenge to the tax collecting state. While scal systems are nationally bounded and inherently static, capital itself is unprecedentedly mobile, uid and fungible. In these terms, nancial derivatives not only challenge default conceptions of the o shore world in International Political Economy, which have predominantly focused on nationally variegated tax systems, but via abstraction recon gure the materiality of contemporary capitalism.